Colonial virtue : the mobility of temperance in Renaissance England - Evans, Kasey, 1976- (University of Toronto Press, 2012)
"Colonial Virtue is the first study to focus on the role played by the virtue of temperance in shaping ethical debates about early English colonialism. Kasey Evans tracks the migration of ideas surrounding temperance from classical and humanist writings through to sixteenth- and seventeenth-century applications, emphasizing the ways in which they have transcended the vocabularies of geography and time.